Hannah Arendt : Life is a Narrative / Julia Kristeva. - Kristeva, Julia (University of Toronto Press, 2018)
In this volume, based on the series of Alexander Lectures she delivered at the University of Toronto, Julia Kristeva explores the philosophical aspects of Hannah Arendt's work: her understanding of such concepts as language, self, body, political space, and life. Kristeva's aim is to clarify contradictions in Arendt's thought as well as correct misapprehensions about her political and philosophical views.The first two chapters describe how Arendt followed an original conception of human narrative, such that life, action, and even thought, are only human when they can be narrated and thus shared with other persons who, through the evocation of memory, complete the story and make history into a condensed sign, into a revelation of the 'who.' The third chapter concentrates on Arendt's work in relation to her twentieth-century contemporaries, especially Isak Dinesen, Brecht, Kafka, and Nathalie Sarraute. In the last two chapters, on the body and the Kantian concept of judgment, Kristeva offers a subtle critical exploration of Arendt's ignoring of the world of the unconscious opened up by psychoanalysis, an exploration that, paradoxically, reveals the political force of Arendt's acceptance of herself as woman and Jew.Kristeva's account of Arendt's 'philosophy of narrative' is clear, coherent, forceful, and often impassioned. Much has been written in North America about Arendt's political work, but little about her more philosophical endeavours. Hannah Arendt: Life Is a Narrative makes a compelling case that Arendt may be the twentieth century's only true political philosopher.
Keywords: Arendt, Hannah, -- 1906-1975.; Arendt, Hannah, -- 1906-1975